2022
DOI: 10.3390/molecules27134048
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Blue Thermally Activated Delayed Fluorescence Emitters Based on Multi-Donor Modified Oxygen-Bridged Boron Acceptor

Abstract: The employment of thermally activated delayed fluorescence (TADF) emitters is one of the most promising ways to realize the external quantum efficiency (EQE) of over 25% for organic light-emitting diodes (OLEDs). In addition, the TADF emitter based on oxygen-bridged boron (BO) fragment can maintain blue emission with high color purity. Herein, we constructed two blue TADF emitters, 3TBO and 5TBO, for OLEDs application. Both emitters consist of three donors linked at the oxygen-bridged boron acceptor. OLED devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The 2,8-bis(diphenylphosphoryl)dibenzo[ b , d ]thiophene (PPT) exhibited a higher triplet energy ( E T = 2.9 eV) in reference to that of Ir( iii ) phosphors or relevant blue emissive TADF emitters. Hence, PPT was employed as both the host and hole-blocking layer, 38 which is expected to facilitate the effective confinement of triplet excitons within the emissive layer (EML) (Fig. S3, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…The 2,8-bis(diphenylphosphoryl)dibenzo[ b , d ]thiophene (PPT) exhibited a higher triplet energy ( E T = 2.9 eV) in reference to that of Ir( iii ) phosphors or relevant blue emissive TADF emitters. Hence, PPT was employed as both the host and hole-blocking layer, 38 which is expected to facilitate the effective confinement of triplet excitons within the emissive layer (EML) (Fig. S3, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al reported TDBA-Cz and DBA-Cz with two carbazole donors that were incorporated into DOBNA, 20 while our group synthesized 3TBO and 5TBO by introducing three carbazole donors into DOBNA. 21 TDBA-Cz and DBA-Cz achieved narrow blue emission in devices ( λ EL = 466/467 nm, FWHM = 47/50 nm), but the emission peaks of 3TBO and 5TBO ( λ EL = 484/484 nm, FWHM = 47/57 nm) had red-shifted due to the additional carbazole donor.…”
Section: Boron-based Da-type Tadf Emittersmentioning
confidence: 95%
“…In addition, the TDBA-Cz exhibited Inspired by the above report, Jiang et al, reported two new blue emitters by introducing additional carbazole donor into the TDBA-Cz core namely, 3TBO and 5TBO. [78] Photophysical analysis revealed that the 5TBO exhibited slightly blue-shifted emission compared to 3TBO attributed to the reduced acceptor strength of DOBNA by additional t-Bu unit. This is also confirmed by the solvatochromic studies, where 3TBO displayed large red-shift with increasing solvent polarity.…”
Section: D-a-d Configured Dobna-based Emittersmentioning
confidence: 99%